Did the Benue Trough connect the Gulf of Guinea with the Tethys Ocean in the Cenomanian? New evidence from the palynostratigraphy of the Yola Sub-basin. (March 2021) - Usman, Musa B.; Brasier, Alexander T.; Jolley, David W.; Abubakar, Usman; Mukkafa, Shehu
Abstract: The Yola Sub-basin represents the lower portion of the bifurcated Upper Benue Trough, whose origin has been linked to the opening of the Atlantic Ocean in the Mesozoic. The sub-basin fill consists predominantly of siliciclastic and carbonate deposits, the ages of which have remained controversial until now. This work employs field observations integrated with palynostratigraphy to refine the stratigraphy of these Upper Cretaceous deposits. We delineate five palynozones, spanning the upper Albian–Cenomanian, middle Cenomanian, upper Cenomanian, Turonian and Coniacian–Santonian. This palynology indicates that rocks previously thought to be Turonian are in fact Cenomanian. Further, the species Florentinia berran, Florentinia khaldunii, and Subtilisphaera senegalensis are all low latitude dinocysts that previously have only been reported from the Tethyan realm. Their presence here, together with the sedimentology, implies that there was an influx of Tethyan waters into the epeiric sea of the Benue Trough in the Cenomanian. The collective sedimentary and palynological evidence indicates that the Cenomanian transgression was well established in the Yola Sub-basin, and more broadly in the Upper Benue Trough, connecting Tethys with the Gulf of Guinea. Highlights: The spores and pollen are characteristic of African, North American and South American province. The palynozones indicate that the stratigraphy of Yola Sub-basin spans from late Albian to Santonian period. Diverse and abundant dinocysts were recorded from the marine strata. The sedimentology and palynozones suggest Cenomanian marine transgression. Correlation with lower Benue Trough and Gongola Sub-basin suggests a link between Tethys Ocean and Gulf of Guinea.